Cost Analysis of RCC, Steel and Composite Multi-Storied Car Parking Subjected to High Wind Exposure in Bangladesh - Kuddus, Mir Abdul; Dey, Partha Pritom (Civil Engineering Journal, 2017)
Steel-concrete composite constructions in Bangladesh are nowadays very popular owing to their advantages over conventional concrete and steel constructions. Concrete structures are massive and allot more seismic weight and less deflection whereas steel structures instruct more deflections and ductility to the structure, which is beneficial in resisting earthquake and wind forces. Composite construction combines the better properties of both steel and concrete along with lesser cost, speedy construction, fire protection etc. The objective of this study was to analysis and design ground floor plus 19 storied R.C.C, Steel and Composite (steel-concrete) multi-storied parking structureâs frame of same plan using ETABS 2013 software and compare their structural parameters with estimated cost for required material. All frames are designed for same gravity and dynamic loadings. The RCC deck-slab is used in steel and composite frame. Beam and column sections are made of RCC, steel or steel-concrete composite sections. The composite construction option provided about 25 % and 18% less cost when compared to RCC and steel structure, respectively. Comparative study concludes that the composite frames are best suited among all the three types of constructions in terms of material cost and benefit added with better structural behaviour.